Clinical characteristics and treatment during preconception and perinatal period of infertile women with non-classical 21-hydroxylase deficiency - Xuejiao Cui; Ping Li (BMC, 2024)
Abstract Objective A single-center observational study to determine the clinical characteristics and therapeutic dose adjustments in women of reproductive age with infertility and non-classical 21-hydroxylase deficiency (NC-21OHD). Design A retrospective analysis of 20 women of reproductive age who were diagnosed with NC-21OHD during an infertility evaluation at Shengjing Hospital of China Medical University from January 2013 to May 2024 was performed. The clinical manifestations, auxiliary examinations, adjustment of glucocorticoid (GC) treatment during preconception and perinatal period, and pregnancy outcomes were analyzed. Results 14 of 16 patients (87.5%) had inappropriately elevated progesterone levels during the follicular phase. The average levels of 17α-hydroxyprogesterone, testosterone, androstenedione, and dehydroepiandrosterone sulfate in the follicular phase were also significantly increased. All 20 infertile patients received GC treatment before preparing for pregnancy. During the follow-up, six of 20 patients had seven conceptions. three patients had spontaneous abortions in the first trimester and four patients delivered babies (4/20). Three patients had a GC dose that was maintained throughout pregnancy and one had an increase in the GC dose starting in the second trimester. Of the remaining 16 patients, seven are still trying to conceive and nine had discontinued treatment. Conclusions An abnormal increase in the follicular phase progesterone level is the most common serologic marker for NC-21OHD among infertile women. Ovulation can be restored after GC treatment, but the proportion of successful conceptions remains low. The dose of GCs in most pregnant women remained unchanged throughout pregnancy.